2(3u-7)=-4(3-2u)

Simple and best practice solution for 2(3u-7)=-4(3-2u) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3u-7)=-4(3-2u) equation:



2(3u-7)=-4(3-2u)
We move all terms to the left:
2(3u-7)-(-4(3-2u))=0
We add all the numbers together, and all the variables
2(3u-7)-(-4(-2u+3))=0
We multiply parentheses
6u-(-4(-2u+3))-14=0
We calculate terms in parentheses: -(-4(-2u+3)), so:
-4(-2u+3)
We multiply parentheses
8u-12
Back to the equation:
-(8u-12)
We get rid of parentheses
6u-8u+12-14=0
We add all the numbers together, and all the variables
-2u-2=0
We move all terms containing u to the left, all other terms to the right
-2u=2
u=2/-2
u=-1

See similar equations:

| 9x-16=10x-10 | | Y=80^c | | -3x+4,X=5 | | 7v+4=4v+22 | | -3-5v=-22 | | 9(x+8)+10=55 | | 29.4+2y=9y+14 | | 2(3u+7)=-4(-3-2u) | | 4w+-5=8w+3 | | 3u+21=7u-15 | | -5+5n=4n-7(n-5) | | 2(3x+6)=2x-12-8x | | 44-3c=29 | | X²+7x+12=6-X² | | 31-2b=25 | | 7a=180° | | 4a+15=23 | | 5x+4=7x+-4 | | 12−3x=5x+30 | | (x+4)/7=5;x=30 | | -3-3(6v+1)=-7v+38 | | 45-y-5*y-5=124 | | -3(2x-6)=4x+8 | | 3x³-27x=0 | | 5y-11-3y+6=0 | | X.3(2x-5)=2(3x-2 | | 3(x+9=7x-6 | | x+2÷9=3 | | 2x-5+x+9+4x-4x-10=180 | | 6(x-1)-5=2x+4(-4+x) | | x/​19.3=7.5 | | 8x-3x=8x |

Equations solver categories